MANTRA: a serious game improving knowledge of maternal and neonatal health and geohazards in Nepal. (13th November 2019) - Mueller, S; Soriano, D; Boscor, A; Saville, N M; Arjyal, A; Baral, S; Fordham, M; Hearn, G J; Kayastha, R; Kostkova, P
Abstract: Background: Mobile technology is increasingly important for delivering public health interventions to remote populations. This research study developed, piloted, and assessed a serious game for mobile devices that teaches geohazard, maternal, and neonatal health messages. This unique mHealth intervention aimed at low-literacy audiences in low resource settings is part of the Maternal and Neonatal Technologies in Rural Areas (MANTRA) project: Increasing maternal and child health resilience before, during, and after disasters using mobile technology in Nepal. Specifically, we assess impact of the serious game to improve knowledge gain in our target audience. Methods: Co-creation with the MANTRA team and local stakeholders in Nepal identified core needs, developed appropriate pictograms and mechanics, and tailored the pilot game to the local cultural context. Through picture matching with immediate audio and visual feedback, the game teaches 28 learning objectives in three modules: maternal health, neonatal health, and geohazards. To assess the game, 35 participants were recruited in Kathmandu and villages in Kavre district. Sessions consisted of pre-test assessment, playing the game, post-test assessment, and a focus group to elicit qualitative feedback. Results: The knowledge assessment quantified knowledge gain. Overall, the group averaged a normalized 6.8 point improvement (p = 0.000022). Change in the geohazard module was 9.5 points (p = 0.001), followed by maternal health (7.4 points, p = 0.007), and neonatal health (4.3 points, p = 0.83). Four learning objectives had statistically significant change (p < 0.05). Feedback demonstrated high engagement, motivation, and usability of the game. Conclusions: This MANTRA study is a unique mhealth intervention of a serious game to teach core health and hazards messages to low-literacy audiences in rural Nepal. The pilot intervention demonstrated statistically significant knowledge improvement among participants. Key messages: The pilot MANTRA mobile serious game intervention is a novel idea, to bring public health knowledge to difficult to reach vulnerable populations, including often ignored illiterate audiences. The pilot MANTRA mobile serious game intervention demonstrated a statistically significant knowledge improvement of geohazard, maternal, and neonatal health learning objectives among participants.